Trouble in Paradise: The Effects of Immigration on Small Island Communities in Thailand - Kolbe, Elizabeth J. (Journal of Human Rights and Peace Studies, 2018)
Immigration is a richly discussed topic in human rights, especially in Asia, however much of the focus is on the immigrants themselves and the conditions faced in the host country. Studies on the impacts of migration (internal and international) on local communities and labor markets yield mixed results. Some scholars (Foged and Peri, 2014; Hall, 2011; Cholewinski and Taran, 2010) remark on the enefits that host countries and counities receie fro irant laor in that it fills laor aret aps helps oost loal copetitieness for the country, and leads to upward mobility in employment for local workers. Others (Abdul-Rahman, et al., 2013; Pholiphirul, 2011; Orrenius and Zavodny, 2005) highlight the negative impacts of migration on the wages of local workers, the ability of local workers to find lucratie eployent as ell as the possile effects of the dependence of countries on migrant work. This paper will discuss the effects of immigration on small island communities in Thailand as related to the author’s master’s thesis. The unique context of small island communities allows for a closer look at the effects that immigration has on a work force due to the fact that other options for employment are not abundant. Unlike communities on the main land that may have access to other employment options, islanders must make the decision to migrate themselves if they wish to seek work in other sectors due to the limited industry on small islands. By analyzing the context of immigration on small island communities that have limited opportunities for upward mobility in employment, reduced access to other labor sectors, and a heavy dependency on tourism development, this paper explores if and how immigration affects the local labor forces and host communities of small island communities in Thailand.